Impacts of Solar Electricity Generation on the Thai Electricity Industry - Wattana, Buncha; Aungyut, Phinyo (International Journal of Renewable Energy Development, 2022)
This paper analyses the impacts of electricity generation from solar energy on the Thai electricity industry. In this paper, three scenarios (REF, Solar2015 and Solar2018) are developed to represent an increased levels of electricity produced from solar energy. A Low Emissions Analysis Platform (LEAP) model is employed, in this paper, to assess the impacts for the period 2019–2037. This paper assesses and analyses the scenario impacts in terms of diversification of electricity generation, fossil fuel requirement and emissions of CO2 and SO2. The analysis reveals that increased electricity generation from solar energy would help diversify energy supply for electricity generation, reduce fossil fuel imports, and therefore help improve energy security of the country. Furthermore, it would help mitigating CO2 and SO2 emissions – an issue of environmental significance. Despite several benefits, there are a number of emerging barriers for promoting electricity generation from solar energy in Thailand. These include the intermittency of solar energy, high-capital cost, unsupportable grid infrastructure and unfavourable regulatory framework. This paper, therefore, suggests that the implementation of energy storage system, provision of financial incentives to potential investors, improvement of grid flexibility and the revision of the regulations to support solar energy business could be effective strategies in order to address the barriers facing the Thai electricity industry.